Flow cytometry in the differential diagnosis of myelodysplastic neoplasm with low blasts and cytopenia of other causes - Márk Plander; Márk Plander; Mária Kányási; Tamás Szendrei; Judit Skrapits; Botond Timár (Frontiers Media S.A., 2024)
BackgroundMyelodysplastic neoplasms (MDS) are characterized by cytopenia, morphologic dysplasia, and genetic abnormalities. Multiparameter flow cytometry (FCM) is recommended in the diagnostic work-up of suspected MDS, but alone is not sufficient to establish the diagnosis. Our aim was to investigate the diagnostic power of FCM in a heterogeneous population of patients with cytopenia, excluding cases with increased blast count.MethodsWe analyzed bone marrow samples from 179 patients with cytopenia (58 MDS, 121 non-MDS) using a standardized 8-color FCM method. We evaluated the sensitivity, specificity, and accuracy of several simple diagnostic approaches, including Ogata score, extended Ogata score, the WHO and ELN iMDSFlow recommended "3 aberrations in two cell compartments method," and the combination of the Ogata score and "3 aberrations in two cell compartments method." The patients were followed until the diagnosis was confirmed, with a median follow-up of 2 months (range 0.2-27).ResultsThe combination of Ogata score and "3 aberrations in two cell compartments method" achieved the highest diagnostic accuracy (78%) with sensitivity and specificity 61% and 86%, respectively. When using only the "3 aberrations in two cell compartments method," the accuracy was 77% with a sensitivity of 72% and a specificity of 79%. The most frequently observed etiologies among the false positive cases were substrate deficiencies, inflammation/infection, or toxic effects. MDS can be excluded in all these cases after a thorough clinical evaluation and a relatively short follow-up.ConclusionFCM remains an important but supplementary part in an integrated diagnostic process of MDS with low blasts. The combination of the Ogata score and the "3 aberrations in two cell compartments method" slightly improves accuracy compared to the detection of "3 aberrations in two cell compartments method" alone.